Enhanced Antihyperglycemic Potential of Rhizophora mucronata Leaf Extract Nanoparticles as a Natural Therapeutic Agent - Hartati, Hartati; Hartono, Hartono; Musawira, Musawira; Khalidatunnisa, Besse; Kusdianawati, Kusdianawati; Isma, Auliana Bestray (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Diabetes mellitus is a long-lasting metabolic condition characterized by elevated levels of glucose in the blood. Rhizophora mucronata, a locally abundant mangrove species in Indonesia, has attracted attention for its potential medicinal properties. The limited effectiveness of conventional herbal preparations has prompted the development of mangrove extract nanoparticles to improve the solubility, stability, and bioavailability of active compounds. This study evaluates the phytochemical profile, physicochemical properties, and antihyperglycemic activity of R. mucronata leaf extract nanoparticles. Phytochemical screening identified secondary metabolites including alkaloids, flavonoids, triterpenoids, tannins, and saponins. SEM analysis revealed irregular, agglomerated nanoparticle morphology, and EDS confirmed that carbon and oxygen were the dominant elements. XRD analysis indicated semi-crystalline characteristics, while FTIR detected key functional groups associated with organic compounds. In vivo experiments using alloxan-induced mice showed that treatment with mangrove extract nanoparticles, especially at a 15% concentration, significantly lowered blood glucose levels compared to other treatments. These findings suggest that mangrove leaf extract nanoparticles hold strong promise as an effective and stable natural antihyperglycemic agent.